The Effect of Task Familiarity Ordering on Listening Task Complexity - Bahman Amini; Abbas Bayat; Keyvan Mahmoodi (Issues in Language Teaching, 2023)
In recent decades, many second language acquisition (SLA) researchers have identified the leading role of organizing sequentially cognitive tasks in Task-Based Language Teaching. Presenting types of different task sequence has become increasingly crucial for syllabus designers. This investigation examines the theoretical basis of task sequencing, which claims that pedagogical tasks should be developed and ordered cognitively from easy to complex. The current study aims to compare the performance of English learners in sequenced and isolated familiar tasks. Sixty EFL learners studying at the intermediate level in two private language institutes participated in this research. They were randomly selected as one experimental and one control group, each comprising 30 subjects. Before starting treatment, all the participants took a listening comprehension test as a pretest. The treatment took place over one semester, during which the subjects performed simple-complex familiar sequenced tasks while the control group received familiar randomized tasks. After treatment, the posttest of listening comprehension, which contained two complex task features, i.e., - Here-and-Now and - Planning time, was employed. The independent-samples t-test showed that the experimental group who received simple-complex sequenced tasks outperformed the control group in listening to complex tasks. The findings supported the employment of simple-complex sequencing tasks to foster listening task complexity performance.